PERUBAHAN STRUKTUR EKONOMI, DEKOMPOSISI SUMBER PERTUMBUHAN OUTPUT, DAN PERTUMBUHAN TOTAL FACTOR PRODUCTIVITY (TFP): Analisis Lanjutan Tabel Input-Output Provinsi Kalimantan Selatan, 2000-2010 - , Nurul Fajri ([Yogyakarta] : Universitas Gadjah Mada, 2013)
High economic growth is the target of economic development in each area. Economic development should be prioritized in sectors that can be a major driver of the economy so that the economy can grow faster. According to sources, economic growth can be seen from the aggregate demand side, namely consumption, investment, government spending, exports and imports, and the aggregate supply side namely labor growth, capital growth and the growth of TFP (Total Factor Productivity). In the long run, economic development will bring a fundamental change in the economic structure. Kuznets define that economic growth is a continuous rise in the product/Output per capita or per worker and is usually accompanied by structural changes (Jhinghan, 2003). Changes in the economic structure of the primary sector to the industrial sector is not only a result of the economic development, but also for sustainable development in the long run. This study uses South Kalimantanâs Input-Output Tables of 2000.2005 and 2010. The results showed that although the structure of the value-added of the mining sector remains the main economic pillar, but this sector has low linkages with other sectors. Based on the forward linkage index, backward linkages indexe and Output multiplier, prime mover and driving economic growth sector are manufacturing sector i.e chemical industry, food, beverages and tobacco industry, rubber and plastics industry, paper, printing and publishing industry and industry of metal, machinery, transport equipment and other manufacturing industries. Based Multiplier Product Matrix, manufacturing industry suggest a dominant role (or leading role) in the economy so that it can be said that the province of South Kalimantan are heading toward a change in the economic structure. Decomposition of sources of growth based on the Cheneryâs model (1960) showed that the main source of economic growth in South Kalimantan is exports by 67 percent in the period 2000-2005 and 73.72 percent in the period 2005-2010, especially the export of coal. Decomposition of productivity growth made by Namura and Kurodaâs model (2004) and suggests that TFP growth and capital have a strong linear relationship and significant Output growth, while labor productivity have no significant correlation with Output growth. Finally, the wealth of the abundant natural resources, industry-oriented economic growth and sustainable development in South Kalimantan Province is agriculture-based industries and mining-based industries with the main strategy is to import substitution and investment in capital and technology.